Analysis of Google users’ interests in information about pacifiers: an ecological digital study - Hagemann, E.; Lotto, M.; Aguirre, P. E. A.; Hoffelder, L.; Petersen, R.; Cruvinel, T.; Rodrigues, J. A. (European archives of paediatric dentistry, 2025)
Purpose To determine the interests of Google users from different countries about pacifier-related information over time, through a quantitative and qualitative analysis. Methods This infodemiology longitudinal retrospective ecological study investigated pacifier-related computational metadata from 22 countries using Google Trends platform. Initially, Relative Search Volume (RSV) time series data and their respective main queries were collected employing the topic “pacifier – subject” as the search strategy from January 2004 to June 2024, considering all categories. Data were then analyzed through seasonal decomposition to determine the trend, seasonal, and residual components of the collected time series using Python 3 programming libraries in a Google Collaboratory interface. Additionally, Mann–Kendall tests were performed to access the significance level of trends observed from the seasonal decomposition. Finally, the queries were qualitatively evaluated to identify the main subjects related to users’ interests. Statistical significance was determined with p values < 0.05. Results In general, RSV time series curves exhibited upward trends in all analyzed countries over the years, with significance levels demonstrated by the Mann–Kendall tests. Moreover, queries often centered around types of pacifiers, encompassing searches specifically for certain commercial brands. Some searches concerning newborn and baby care were also observed, particularly highlighting breastfeeding practices. Conclusion Google users have shown an increasing interest in pacifier-related topics. These data can help understand the needs and concerns of parents and caregivers regarding pacifier use, ultimately supporting the development of effective educational strategies.